Identifikasi Molekuler Gurita (Family: Octopodidae) dari Perairan Lombok Berdasarkan Marka Gen Sitokrom Oksidase Sub Unit I - Mulyani, Laily Fitriani; Mukhlis, Alis; Marzuki, Muhammad; Cokrowati, Nunik; Diniarti, Nanda; Yonita, Nuansa Azma (Universitas Teuku Umar, 2025)
Lombok waters are a potential commodity area for fishing. One of the potential commodities caught is the octopus species from the octopodidae family. A recent study revised the generic taxonomy of the Octopodidae family, and several groups of species previously included in Octopus are now recognized as independent genera. However, knowledge of the phylogenetic relationships among taxa in the Octopodidae family is still lacking. This study aims to identify octopuses belonging to the genus Octopus in Lombok Waters, namely: Sari Gong Beach, Ketapang Beach, Beraringan Beach, Cemara Lembar Beach molecularly. The study was conducted from January to June 2024. Octopus samples caught by fishermen were analyzed morphologically and molecularly. The study will be conducted for 6 months from January to June 2024 in Lombok Waters. Octopus sampling was carried out once a month, observations representing the conditions of the dry season and rainy season with an interval of 30 days. The research methods used include: octopus sampling, identification, molecular identification, alignment of 16S rRNA gene nucleotide sequences, genetic distance. It is hoped that this study will be useful for providing basic information on octopus species belonging to the genus Octopus found in Lombok Waters. This information can be used for further studies on octopus biology, octopus resource potential, and studies on octopus resource management strategies in Lombok Waters. The octopus species caught in Lombok Waters were identified morphologically and molecularly as Octopus cyanea. In addition, the nucleotide base sequence can be used to design specific COI gene primers for O. cyanea